Eyeing the Future of Agriculture : A Vision for Agricultural Innovation in Chile - Janssen, Willem (World Bank, Washington, DC, 2012)
Chile is one of the leading agricultural producers in Latin America and an important player in world agro-alimentary markets-a position it is determined to maintain. In 2008, the government (through the Ministry of Agriculture) requested technical assistance from the World Bank to define how agricultural innovation can help maintain future competitiveness and how it needs to evolve. However, since changes in its agricultural innovation system will pay off more in the long run than in the short term, Chile needed a realistic assessment of what it will take to be an agricultural leader in the future, knowing that without an understanding of the future, any major investment in agricultural innovation would be like shooting a cannon in the dark. Although many dynamic changes (such as population growth, improved incomes, market development, climate change, shifting dietary patterns, and advances in technology) can be identified, mapping and tracing their interaction is highly complex. So the Ministry and the Bank jointly engaged in a visioning exercise to understand the factors that drive Chile's agricultural future. This smart lesson summarizes that exercise and shares some of the lessons learned.